Implementation of Reliability Maintenance (RCM) for Extending Life of Compressors in Ship Repair Yard - ALAWADHI, HAROON ABDULRAZZAQ MOHAMMED (2023)
This study aims to investigate the implementation of Reliability Centered Maintenance (RCM) for extending the life of critical aging assets using in the case study on the compressor used for compressed air supply in the shipyard. RCM is the systematic and proactive technique to optimize the maintenance strategy of assets or systems based on the function, failure, and consequences. RCM helped to prevent and mitigate the potential failure and its effects on the system performance, safety, economy, and the environment, and it extended the asset's life. This study has followed a seven-step RCM methodology to implement the study. This study also used tools like failure mode, failure mode effect, and critical analysis through FMECA and the Risk priority number (RPN) to consider the failure mode and select the most suitable maintenance task. This study also proposed the reliability cycle for the continuous improvement process in RCM. This study found that RCM also helped to determine critical equipment or elements that eliminate failures, keep the equipment healthy for a longer period, and extend assets' life. Moreover, this study also determined some of the challenges and limitations of the RCM implementation, such as budget and resource constraints, management support and commitment, data quality, and the availability of empirical evidence. This study concluded with some recommendations for overcoming these challenges and their limitations, like constructing the cost of benefit analysis that obtains stakeholder involvement and feedback, developing a clear and consistent procedure for the implementation, and conducting more research to provide with further evidence for the RCM's ability to extend asset life.